Evolution of women’s role in the European Union - Latin America and The Caribbean relations - Recavarren Malpartida, Isabel (2023)
This article deals with the unfinished relationship of Gender Equality in bi-regional relations between the European Union and Latin America and the Caribbean. The presence and proposals emanated during the XVII Interparliamentary Conferences (from 1974 to 2005) changed radically after the constitution of the EUROLAT Parliamentary Assembly (2006) and with the content of the EU-LAC Declarations since 1999. A proposal of the Civil Society-Academy to the Social Commission of the EUROLAT Assembly, generated the creation of the Euro-Latin American Women’s Forum coordinated by the proponents at the request of said Assembly. A coordination of two legislatures. Women in power, such as Baroness Catherine Ashton, reinforce the proposal with the creation of the Gender Chapter that takes up the original proposal. Despite the interruption of biregional relations, the Chapter proposed to act with a governmental spirit. The recent EU-CELAC 2023 Declaration tends to involve citizens.